Bioaerosol cellular responses to survive mechanical stress - King, Maria D.; Smith, Brooke (Henry Stewart Talks, 2024)
Definition of bioaerosols, Bioaerosols and health, Environmental stressors, Cellular responses to stress, Gene expression after aerosolization, Protein activity after aerosolization, Quiescence, Aerosolization and antibiotic resistance